Balinese Language on the Street Signs in Singaraja Town, Bali: A Linguistic Landscape Analysis - I Made Suta Paramarta (Ranah: Jurnal Kajian Bahasa, 2022)
The existence of local languages in Indonesia, including Balinese language is often related to marginalization issue. Some previous research revealed that Balinese language is rarely used in public spaces. The local government implements Governor Regulation Number 80 of 2018 to officially protect the language, including its existence in public spaces. This research explores the existence of Balinese language and script on the lingual street signs in Singaraja, North Bali. Further, the distribution of the lingual street signs is also investigated to reveal the government's primary and secondary target areas in language protection. The subjects of the study are 151 street signs that are placed by the department of transportation of Buleleng regency. The data are obtained through photograph taking and observation. The research reveals that the presence of Indonesian language marginalizes Balinese language. The regulation only successfully improves the use of Balinese script instead of the use of Balinese language. In terms of the sign distribution, the government focuses on signs with Balinese script at the center of the town due to the intense language contact in the area.  AbstrakKeberadaan bahasa daerah di Indonesia, termasuk bahasa Bali sering dihubungkan dengan isu marginalisasi. Beberapa penelitian sebelumnya mengungkapkan bahwa bahasa Bali jarang digunakan di ruang publik. Pemerintah daerah Bali telah menerapkan Peraturan Gubernur Nomor 80 Tahun 2018 untuk secara resmi melindungi bahasa dan aksara Bali, termasuk keberadaannya di ruang publik. Sehubungan dengan itu, penelitian ini menggali keberadaan bahasa dan aksara Bali pada rambu-rambu jalan lingual di Singaraja, Bali Utara. Selanjutnya, sebaran rambu-rambu jalan lingual juga diselidiki untuk mengungkap wilayah sasaran primer dan sekunder pemerintah dalam perlindungan bahasa Bali. Subyek penelitian adalah 151 rambu jalan yang dipasang oleh Dinas Perhubungan Kabupaten Buleleng. Data diperoleh melalui pengambilan foto dan observasi. Hasil penelitian mengungkapkan bahwa bahasa Bali terpinggirkan dengan kehadiran bahasa Indonesia. Peraturan gubernur tersebut hanya berhasil meningkatkan penggunaan aksara Bali ketimbang penggunaan bahasa Bali. Dalam hal distribusi tanda, pemerintah memfokuskan penggunaan tanda dengan aksara Bali di pusat kota karena kontak bahasa yang intens terjadi di daerah tersebut.